Organizational citizenship behavior as a model of participation building a dialog among knowledge (2018)
The aim of this documentary research was to compare the constructs of community, participation, organization, organizational citizenship behavior (OCB) and knowledge dialogue; in order to recognize whether citizenship behaviors are examples of participation; and if them bring of the dialogue of knowledge into management environment. Making use of the content analysis technique, we analyzed and interpreted the comments made by different authors, concluding that OCB represent a form of voluntary participation; based on human-male interaction, promoting decisionsmaking; supported by a dialogical relationship.